Dual community assembly processes in dryland biocrust communities. (6th February 2020) - Soliveres, Santiago; Eldridge, David J.
Abstract: Biocrusts are critical components of drylands where they regulate a wide range of ecosystem functions, however, their response to the world‐wide phenomenon of shrub encroachment and to livestock grazing, the most extensive land use in drylands, is not well studied. Grazing by livestock and increases in shrub cover could influence biocrust communities directly via trampling or shading, or indirectly, by altering biotic interactions amongst biocrust taxa. The extent of these changes in biocrust cover, diversity and composition are poorly known. We used linear models and structural equation modelling to examine the direct effects of grazing and shrubs on biocrust community composition and the indirect effects mediated by changes in species interactions. Biocrust richness and cover increased with increasing shrub cover at the site level. This pattern occurred despite the negative response we found (lower cover and richness) under shrub patches versus open areas, which was consistent irrespective of the grazing level. Functional diversity and evenness were similar between shrubs and open at low grazing intensity, but at high grazing functional diversity was greater in the open. Competition between biocrust species was an important driver of their community assembly irrespective of shrub cover, grazing intensity or patch type. Structural equation models showed that the effects of grazing and shrub cover on functional evenness, functional diversity and richness were controlled by biotic interactions within the shrub microsites. In the open, however, these effects were either direct or mediated by changes in cover. Biocrust cover, species richness and functional diversity increase with shrub cover at the site scale, despite the negative effects at the microsite level. We demonstrate here that drivers of community assembly differ markedly at small spatial scales. Though biocrust communities were directly driven by environmental filtering in the open, biotic interactions played a fundamental role in their assembly when growing beneath shrubs. A free plain language summary can be found within the Supporting Information of this article. Abstract : A free plain language summary can be found within the Supporting Information of this article.